Elaboração de bionanocompósito quitosana/nanofibra de celulose e seu efeito sobre a qualidade de morangos - Resende, Nathane Silva (2015)
Strawberries are fruits highly appreciated by consumers due their sensory and nutritional characteristics. Among them, the intense red color and the characteristic aroma, plus the texture and slightly sour flavor. In what concerns the nutritional attributes have low caloric intake and antioxidant activity. The implementation of technologies to increase the time of strawberries postharvest life is important, since it can make your marketing more viable, reducing losses and leading to an increased farmer income. Thus, the southern region of Minas Gerais, where are concentrated the major producers of fruit, can benefit. Research interest by chitosan has grown steeply in recent years, that thanks to the research carried out in the area that confirm the excellent properties of this substance to form films, providing a very effective barrier on the surface of the fruit. Studies show that it is a compound nontoxic, safe and antimicrobial properties well described in the literature. The cellulose nanofibers derived from renewable sources have been focus to several authors of research in recent years. The main interest is the mechanical properties of these structures. The aim of this study was to develop bionanocomposites chitosan / cellulose nanofiber and study its effect on the postharvest quality of strawberries. The use of bionanocomposites chitosan / cellulose nanofiber produced in this work is a good alternative for the control of respiratory processes, oxidation and dehydration, directly influencing the properties such as texture, consistency, microbial growth and shelf life.